Synergistic Effect of Hybrid PbS Quantum Dots/2D‐WSe2 Toward High Performance and Broadband Phototransistors. (16th November 2016) - Hu, Chao; Dong, Dongdong; Yang, Xiaokun; Qiao, Keke; Yang, Dun; Deng, Hui; Yuan, Shengjie; Khan, Jahangeer; Lan, Yang; Song, Haisheng; Tang, Jiang
Abstract : The transitionmetal dichalcogenides‐based phototransistors have demonstrated high transport mobility but are limited to poor photoresponse, which greatly blocks their applications in optoelectronic fields. Here, light sensitive PbS colloidal quantum dots (QDs) combined with 2D WSe2 to develop hybrid QDs/2D‐WSe2 phototransistors for high performance and broadband photodetection are utilized. The device shows a responsivity up to 2 × 10 5 A W –1, which is orders of magnitude higher than the counterpart of individual material‐based devices. The detection spectra of hybrid devices can be extended to near infrared similar to QDs' response. The high performance of hybrid 0D‐2D phototransistor is ascribed to the synergistic function of photogating effect. PbS QDs can efficiently absorb the input illumination and 2D WSe2 supports a transport expressway for injected photocarriers. The hybrid phototransistors obtain a specific detectivity over 10 13 Jones in both ON and OFF state in contrast to the depleted working state (OFF) for other reported QDs/2D phototransistors. The present device construction strategy, photogating enhanced performance, and robust device working conditions contain high potential for future optoelectronic devices. Abstract : High performance hybrid phototransistors for broadband detection based on PbS QDs and 2D WSe2 monolayer are demonstrated. Owing to the synergistic effect of high mobility of WSe2 nanosheet and strong light absorption of PbS QD layer, high responsivity of up to 10 5 A W –1 is achieved. Further study unfolds the main mechanism, which is attributed to the photogating effect.